The use of SCoT markers for evaluation of the genetic variability of Russian fescue and festulolium varieties - Mavlyutov, Yulian M.; Korovina, Valentina L.; Klimenko, Irina A. (Experimental Biology and Biotechnology, 2022)
Forage gramineous grasses are the most important component of the hay lands and pasture agroecosystems. To increase the efficiency of grass breeding the complex evaluation of the initial plant material is necessary, including an application of the current DNA technologies. The aim of this study was to investigate the effectiveness of SCoT markers for PCR-analysis of interspecies and intervarietal genetic variations of Russian fescue (Festuca) and festulolium (× Festulolium F. Aschers. et Graebn.) varieties. Total 13 samples, combined 30 seedlings per variety were genotyped with 25 SCoT markers, indicated as informative for gramineous grasses according to literature sources. The high efficiency of SCoT marking technique as a tool for DNA polymorphism revealing was found for Russian fescue and festulolium species and varieties. The obtained results can be used at the varieties identification and genetic certification as well as for selection the parental forms for the breeding process.
Keywords: fescue; festulolium; genetic diversity; SCoT markers; DNA polymorphism; genotyping